The Reliance of the Jordanian Youth on the Social Media Networks in Promoting the Culture of Dialogue - Lafee Alhammad, Khalaf; Al Olaimat, Farhan; Yahya Bader Al Hadeed, Ali (International Journal of Psychosocial Rehabilitation, 2020)
The study aimed to find out the extent to which the Jordanian university’s youth relied on social networks to establish a culture of dialogue between each other. The study relied on the theory of dependence on the media. The survey methodology was used in a simple random sample of Jordanian university youth. Its size is 400. The results indicated that there are different aspects of the commitment of the Jordanian university youth to the ethics of the culture of dialogue and ethics on the social networks. The first place was for the acceptance of opinion and the other opinion (35.8%), and in the last place, "Tolerance during the dialogue between young people on social networks" (19.3%) The findings also indicated that there are many institutions responsible for establishing a culture of dialogue among Jordanian youth; the family was in the first place (71.5%), then the educational institutions (65.5%), then the media (52%), followed by religious institutions (32.3%), and in the last place, the political institutions (18.8%).